Utilization of Syngas as Co-firing Fuel for Carbonization of Arabica Coffee Pulp - Rizqon Hasibuan; Adi Setiawan; Faisal Faisal (Journal of Engineering and Technological Sciences, 2024)
Pyrolysis is a commonly used method to produce main products such as bio-char, bio-oil and syngas. However, the practical use of syngas as a fuel is currently constrained by suboptimal properties and the necessity for specialized storage. This study investigated the impact of using syngas directly as an additional fuel for heating the pyrolysis reactor on process parameters and the properties of the resulting bio-char products. The experiment was conducted using two process variations: (i) pyrolysis utilizing syngas as fuel for co-firing with LPG, and (ii) pyrolysis using only LPG as fuel. The variables observed during the testing included the consumption of LPG fuel, process time, heating rate, pyrolysis product yields, and the properties of the bio-char. Characterization of the bio-char was carried out through proximate analysis, bomb calorimetry, thermogravimetric and FTIR analysis. Based on the experimental results it can be concluded that co-firing is able to save on the use of LPG and reduce process time. In terms of product yield, there was no significant difference when syngas was co-fired with LPG. In terms of the properties of the bio-char product, syngas co-firing pyrolysis helps in reducing the moisture content, increasing the fixed carbon content, and also increasing the calorific value up to 26855 J/g.